Arthropod and Disease Management in Fraser Fir (Pinales: Pinaceae) Christmas Trees in the Southeastern United States. Issue 1 (17th March 2022) - Darr, Molly N; Coyle, David R; Jetton, Robert M
Abstract: Fraser fir, Abies fraseri [Pursh] Poir ., is one of the most desired Christmas tree species owing to its fragrance, physical appearance, and durability. This species represents a major component of the Christmas tree industry in the southeastern United States, with production occurring in North Carolina, Tennessee, and Virginia. Fraser fir production is a multi-million dollar annual industry despite growing in a limited elevational and latitudinal range. Pest management for Christmas trees is notoriously difficult owing to the near zero-tolerance of most pests, even those causing aesthetic damage. Christmas trees are produced in monocultural environments which make them highly susceptible to several arthropod and fungal pests. We review the major pests affecting Fraser fir Christmas tree production, including their biology, symptoms, and scouting procedures, and current management strategies. In general, pest management in Christmas tree production systems has not changed significantly in the last several decades, and still relies heavily on pesticide usage. We propose several areas in need of research that could help Fraser fir Christmas tree producers mitigate the impacts of climate change and potential new pest species, as well as suggest changes to current or potentially novel integrated pest management strategies which have a chance to provide economic and ecological benefits for this industry.